Age of empires - Lipschits, Oded, 1963- (University Park, Pennsylvania : [Tel Aviv, Israel])
xii, 237 sayfa
Keywords: “Examines the administrative system and function of stamp impressions on storage jars in ancient Israel, illustrating the history of Judah during six centuries of subjugation to the empires that ruled the region“ --